Ultra Wide Band Receiver Design - Škapa, Jiří; Pola, Marek (IEEE (Institute of Electrical and Electronics Engineers), 2016)
This paper deals with our Ultra Wide Band (UWB) receiver which is designed for precise indoor localization of fire fight- ers and members of the rescue teams. The purpose of this indoor positioning system is to search for UWB transmitters in a given area and to determine their position. This article de- scribes not only the hardware design of the UWB receiver but also the FPGA firmware development. The described hard- ware is also focused on the development of algorithms and creating signal records used during the real positioning sys- tem development. The design of our UWB receiver considers many requirements such as wide bandwidth, high ADC sam- pling rate, high speed digital buses, high speed digital inter- faces and being made of low cost parts. The results of our simulations show that UWB receiver we proposed is suitable for this application and the hardware and firmware is able to fulfill our requirements. New functions and new signal pro- cessing algorithms can be easily added to the FPGA firmware in the future.
Návrh ultra-širokopásmového přijímače
Keywords: UWB, Indoor, Localization, FPGA, TDOA; UWB, FPGA, lokalizace v budovách